The role of expectation: attention in cognitive performance lab study - Wong, Cheryl Qi Yin (Nanyang Technological University, 2023)
Past studies have found that sudden, loud noise could distract individuals and impair behavioural performance in human participants. By contrast, it has been proven that temporal expectation can enhance performance. As existing literature on the effects of temporal expectation of auditory distractors is sparse, an experimental study was conducted to explore how temporal cueing of noise bursts could influence cognitive performance in a sustained attention task. The aim of this study was to investigate the effects of three noise conditions on cognitive performance: silent condition (C1), unexpected distractors condition (C2), and expected distractors condition (C3). A total of 35 participants were tested in a within-subject design. Distractors were defined by random 80 dB tones lasting 3 seconds. Expected distractors were defined by a click sound occurring 1.5 seconds before each distractor tone. Cognitive performance was measured using reaction time and error rate on a response inhibition task. The Friedman test was conducted to compare the mean scores between the three conditions, to determine the effect of noise conditions on the dependent variables, reaction time and error rate. However, results revealed that the noise conditions had no significant effect on either reaction time or accuracy exhibited during the cognitive task. These results are in contrast with the notion that auditory distractors have disruptive effects on performance efficiency, and that preparatory processes elicited by cues could prevent distraction. Nevertheless, by drawing a link between temporal anticipatory processes and cognitive performance, this study contributes to current understanding regarding attentional and perceptual mechanisms, thus providing relevant insights to researchers who aim to investigate the prevention of distraction.